THE ROLE OF THE OFFICE OF THE PRESIDENT OF UKRAINE UNDER MARTIAL LAW: INSTITUTIONAL AND POLITICAL ASPECTS - Shkuro, Anton (Public Management and Policy, 2026)
The relevance of the topic stems from the increasing concentration of managerial decision-making within the presidential vertical of power following the outbreak of full-scale war, as well as the necessity of understanding the mechanisms by which the Office of the President of Ukraine influences the process of shaping and implementing state policy. Under martial law, the Office of the President of Ukraine no longer performs exclusively administrative and organizational functions but has acquired the features of a strategic center for coordinating political, security, and communication processes. The purpose of the article is to identify the peculiarities of the functioning of the Office of the President of Ukraine under martial law, to analyze the mechanisms of its influence on political decision-making, and to compare the current model of the Office of the President of Ukraine with the previous model of the Administration of the President of Ukraine. The methodological basis of the study includes institutional, systemic, comparative, and structural-functional analyses, as well as content analysis of documents and scholarly works in the fields of public administration, political science, and constitutional law on the functioning of the presidency under crisis conditions. It was determined that, under martial law, the Office of the President of Ukraine serves as an integrating administrative center, ensuring interaction among the security sector, executive authorities, parliament, and international partners. It was substantiated that the current model of the Office of the President of Ukraine’s functioning is characterized by a high level of centralization of managerial processes and operational decision-making, and by the strengthening of the analytical component of its activities. The comparison between the Administration of the President of Ukraine and the Office of the President of Ukraine enabled the identification of a transformation of the presidential apparatus from a predominantly administrative model to a political-coordination system of governance. It was established that the institutional transformation of the Office of the President of Ukraine became one of the key factors in adapting the public administration system to the conditions of martial law. The strengthening of the Office of the President of Ukraine reflects broader trends toward the centralization of political coordination and the concentration of managerial functions within the presidential vertical of power. At the same time, the necessity of ensuring a balance of powers, effective political governance, and democratic oversight in the functioning of the state during crisis conditions is becoming increasingly relevant.